Developing a servicelearning module for oral health: A needs assessment - R Ebrahim; H Julie (South African Medical Association, 2017)
Background. Service learning (SL) as a pedagogy in higher education must be differentiated from other services with a primarily philanthropic intent.Â Dental therapy and oral hygiene students at Sefako Makgatho Health Sciences University, School of Oral Health Sciences, Pretoria, South AfricaÂ visit community sites during their 2nd year of study. However, the current curricula would need restructuring for alignment with the espousedÂ pedagogy and standards of SL. Such an SL curriculum design would thus allow for the provision of meaningful services to communities as an integralÂ component of these programmes.Objective. To explore (i) perceptions of 2nd-year oral health students; and (ii) opinions of academics with regard to the need for an SL module.Methods. Purposive sampling was used to conduct two focus group discussions with academics involved in curriculum development (n=11) andÂ students who had previous exposure to communities (n=10). A survey containing open-ended questions was completed by 9 academics, who wouldÂ implement the proposed SL module. Frequencies were calculated and data from the open questions were analysed for emergent themes.Results. Most academics (89%, n=8) indicated that working effectively with others as members of a team and developing cultural sensitivity wereÂ achievable from an SL module. Two themes emerged from the focus groups, i.e. (i) enhanced teaching and learning â€" students could apply theoreticalÂ and clinical training in an authentic setting; and (ii) standardisation of training â€" an SL module would ensure consistency when engaging withÂ communities.Conclusion. The needs assessment was valuable to inform the development and implementation of the SL module.